Peran Marketing Mix Dalam Meningkatkan Penjualan Pada Usaha Handphone Toko Atlantis Jempong Baru Mataram - Leony Dwi Putri Handayani; Yusi Faizathul Octavia; Surahman Hidayat (Kredibel: Jurnal Ilmiah Manajemen, 2024)
Atlantis mobile phone store is the cheapest and most complete mobile phone store in the city of Mataram, which has been established since 2017 and has branches in various places. Atlantis is a mobile phone store that is quite famous in Mataram City so that many people and students shop. This study aims to find out the role of marketing mix in increasing sales in the cellphone business of Atlantis Jempong Baru Mataram and to find out the effectiveness of marketing mix on cellphone sales of Atlantis Jempong Baru Mataram store. The method used is a qualitative approach with data collection techniques using interviews, observations and documentation. The results of the study show that the role of the marketing mix carried out by the Atlantis mobile phone store consists of the main products are cellphones and mobile phone accessories for prince depending on the choice of type of goods, for the store place is very strategic because it is in the middle of the city, store promotion uses a full strategy by using promotional tools consisting of sules promotion activities, holding displays, installing outdoor adversetting and using two types of promotion, namely personal Alternate and Mass Alternate Meanwhile, in the effectiveness of the marketing mix, the most important role in increasing sales is promotion.